A kind of graphene-based solvent-free wear-resistant drag-reducing coating and preparation method thereof
Through the modification and magnetization pressurization technology of graphene-based solvent-free coatings, the deficiencies of existing coatings in terms of wear resistance, anti-corrosion and drag reduction are solved, and high-performance coating applications are realized, which are suitable for a variety of environments and Reduced construction costs and time.
Patent Information
- Application Number
- CN202411677989.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing solvent-free epoxy coatings have poor performance in wear resistance, shielding and corrosion resistance, and have problems of brittleness and cracking, which limits their application areas.
Using graphene-based solvent-free coating, through the combination of modified graphene powder and sulfomethylated fulvic acid carbon nanosheets, using magnetization and instantaneous pressure technology, a stable and dense coating structure is formed to improve wear resistance and Anti-corrosion properties.
It achieves the super wear resistance, anti-corrosion performance and drag reduction effect of the coating, solves the problems of pus and cracking of traditional coatings, is suitable for a variety of corrosive environments, and reduces construction costs and time.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, and in particular to a graphene-based solvent-free wear-resistant drag-reducing coating and a preparation method thereof. Background Art
[0002] At present, drag-reducing inner coatings at home and abroad basically use solvent-based epoxy coatings with organic solvents as dispersion media. The organic solvents (VOC) volatilized during the coating process account for 30%-50% of the total weight of the coating. VOC is not only harmful to human health, but also may pollute the natural environment. When solvent-free epoxy coatings are cured to form a film, the active solvent also participates in the reaction and becomes a component of the coating, but no solvent evaporates during the construction process, which reduces the emission of VOC in the atmosphere and can better meet environmental protection requirements. In addition, the mechanical properties and chemical resistance of solvent-free epoxy coatings are significantly better than those of solvent-based epoxy coatings, and the mechanical properties such as wear resistance, adhesion, and shear strength are particularly outstanding.
[0003] At present, the existing solvent-free epoxy coating mainly adopts the solvent-free epoxy coating made by the reaction of high molecular epoxy resin and alicyclic amine modified polyamide. For example, high molecular epoxy resin, epoxy functional group active diluent, polyamide wax, titanium dioxide are used as paint components, and alicyclic amine modified polyamide is used as curing agent component. However, since it completely relies on the hardness of the paint film generated by cross-linking reaction to solve the problem of wear resistance, it leads to poor wear resistance; it completely relies on pigments and epoxy resins to solve the problem of coating shielding, and its shielding is also poor; in addition, the paint film formed directly by the reaction of alicyclic amine modified polyamide and epoxy has poor corrosion resistance and low drag reduction. At the same time, the existing traditional solvent-free coatings have the problems of brittleness and cracking.
[0004] Graphene is composed of carbon atoms SP 2 The two-dimensional hexagonal structure of hybridization is tightly packed, and the connection between carbon atoms is flexible. When subjected to mechanical external force, the graphene layer deforms and bends, but the position of carbon atoms does not rearrange, which ensures the stability of the structure. It is precisely because of the graphene lattice structure that it has good flexibility and adhesion properties.
[0005] At present, there are many studies on solvent-free epoxy coatings developed based on graphene, such as CN112029382B, CN112538313B, CN110499086A, CN112080187A, etc., which are all solvent-free coatings prepared based on graphene, with excellent mechanical properties, significantly improving anti-corrosion performance, flexibility and impact resistance, etc., but the drag reduction effect of the coating is unknown, and its application field is limited. Coatings with excellent drag reduction performance can reduce pipeline pressure, friction coefficient and transportation power consumption. Although CN108373738A reports a graphene-based solvent-free internal drag reduction coating, its composition is complex, and the construction time and construction cost are unsatisfactory.
[0006] Therefore, it is of practical significance to develop a solvent-free epoxy coating based on graphene that has excellent corrosion resistance, wear resistance and drag reduction properties, so as to improve construction efficiency and reduce construction costs. Summary of the invention
[0007] In view of this, the present invention proposes a graphene-based solvent-free wear-resistant and drag-reducing coating and a preparation method thereof.
[0008] The technical solution of the present invention is achieved in this way:
[0009] A graphene-based solvent-free wear-resistant drag-reducing coating comprises the following raw materials in parts by weight: 40-60 parts of resin, 5-10 parts of modified graphene powder, 5-10 parts of sulfomethylated fulvic acid carbon nanosheets, 2-4 parts of polymer emulsion, 1-3 parts of silicon dioxide, 0.5-0.8 parts of defoaming agent, and 6-9 parts of curing agent;
[0010] Wherein, the resin is composed of fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:1-2;
[0011] The modified graphene powder includes amino-modified graphene powder and alkyl-modified graphene powder in a mass ratio of 1:3-5;
[0012] The preparation method of the amino-modified graphene powder comprises: adding graphene into anhydrous ethanol, adding (3-aminopropyl)triethoxysilane for activation, washing and drying to obtain;
[0013] The preparation method of the alkyl-modified graphene powder comprises: adding graphene to an acid solution for condensation and reflux, washing and drying to obtain powder, adding the powder to anhydrous ethanol, adding trimethylsilyl chloride, ultrasonically stirring, washing and drying to obtain the powder;
[0014] The preparation method of the sulfomethylated fulvic acid carbon nanosheets comprises:
[0015] (1) adding fulvic acid into a sodium hydroxide solution for immersion, filtering, and obtaining pretreated fulvic acid;
[0016] (2) adding the pretreated fulvic acid to the formaldehyde aqueous solution, heating the reaction, adding sodium pyrosulfite, continuing to heat the reaction, filtering and drying, and obtaining sulfomethylated fulvic acid;
[0017] (3) Add sulfomethylated fulvic acid into anhydrous ethanol, perform ultrasonic treatment, filter, freeze-dry, and calcine under a nitrogen atmosphere to obtain sulfomethylated fulvic acid carbon nanosheets.
[0018] Furthermore, the solid-liquid ratio of the graphene to anhydrous ethanol is 1:50-100 g / mL; the liquid-solid ratio of the (3-aminopropyl)triethoxysilane to graphene is 3-5:1 ml / g; and the activation is performed at 70-80° C. for 6-10 hours.
[0019] Furthermore, in the preparation method of alkyl-modified graphene powder, the solid-liquid ratio of the graphene to the acid solution is 1:60-80 g / mL; the concentration of the acid solution is 0.05-0.1 mol / L; the acid solution is any one of hydrochloric acid, sulfuric acid or nitric acid; the reflux temperature is 80-100°C, and the time is 5-7h; the solid-liquid ratio of the powder to anhydrous ethanol is 1:50-70 g / mL; the liquid-solid ratio of trimethylchlorosilane to powder is 3-5:1 ml / g; and the ultrasonic stirring is performed at 40-60kHz and 40-60°C for 6-10h.
[0020] Furthermore, in the preparation method of sulfomethylated fulvic acid carbon nanosheets in step (1), the solid-liquid ratio of fulvic acid to sodium hydroxide solution is 1:10-20 g / mL; the concentration of the sodium hydroxide solution is 0.05-0.1 mol / L; the impregnation is carried out at 20-25° C. for 10-12 hours;
[0021] In step (2), the solid-liquid ratio of the pretreated fulvic acid to the formaldehyde aqueous solution is 1:5-7 g / mL; the concentration of the formaldehyde aqueous solution is 20-30 wt%; the temperature-raising reaction is carried out at 40-60° C. for 30-60 min; the mass ratio of the sodium pyrosulfite to the pretreated fulvic acid is 0.3-0.5:1; and the continued temperature-raising reaction is carried out at 70-80° C. for 2-4 h;
[0022] In step (3), the solid-liquid ratio of the sulfomethylated fulvic acid to anhydrous ethanol is 1:20-50 g / mL; the ultrasonic treatment is performed at 200-300 rpm and 30-40° C. for 2-4 hours; the calcination temperature is 400-500° C. and the calcination time is 30-60 minutes.
[0023] Furthermore, the polymer emulsion is an acrylic emulsion or a polyurethane emulsion.
[0024] A method for preparing a graphene-based solvent-free wear-resistant and drag-reducing coating, the specific preparation steps are as follows:
[0025] (1) mixing and oscillating the modified graphene powder and a polymer emulsion having a formula amount of 30-50 wt%, and simultaneously irradiating with microwaves to obtain a dispersion a;
[0026] (2) mixing and oscillating the sulfomethylated fulvic acid carbon nanosheets and the remaining polymer emulsion, and simultaneously irradiating with microwaves to obtain a dispersion b;
[0027] (3) magnetizing the dispersion a and the dispersion b, instantaneously pressurizing them after magnetization, filtering and drying them to obtain a mixture;
[0028] (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0029] Furthermore, in steps (1) and (2), the oscillation is performed at 2000-3000 rpm for 10-20 min; the power of the microwave radiation is 400-600 W, and the time is 5-10 min.
[0030] Furthermore, in step (3), the intensity of the magnetization treatment is 100-200 Gs, and the time is 20-30 min; the pressure of the instantaneous pressurization is 10-20 MPa, and the time is 5-8 min.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The graphene solvent-free wear-resistant and drag-reducing coating of the present invention exhibits super wear resistance, which is more than 2.5 times higher than the standard requirements. It solves the problems of brittleness and cracking of traditional solvent-free coatings while improving adhesion. Secondly, the coating film of the present invention is dense and has a smooth surface, which reduces the flow resistance between the medium and the coating surface, improves the speed and efficiency of medium transportation, and has a significant drag reduction effect. Under a circulating temperature environment, it has good flexibility, and the paint film is not easy to crack and fall off, thereby extending the life of the pipeline. In addition, the coating of the present invention is impermeable, delaying the intrusion of corrosion factors into the surface of the substrate, and exhibits super corrosion resistance. It is suitable for various corrosive environments such as extremely corrosive atmospheric environments, seawater, fresh water, drinking water, soil burial, acid and alkali chemical immersion, and is suitable for environments of -25°C to 90°C.
[0033] 2. The graphene solvent-free wear-resistant drag-reducing coating of the present invention is safe and environmentally friendly, has zero VOC, does not contain solvents, heavy metals and coal tar, and does not pollute the environment. It can be quickly cured at room temperature, and can be cured underwater immediately after the coating is applied, without the precipitation of harmful substances. It has a solid content of nearly 100%, and its thick coating characteristics greatly shorten the construction time and reduce the construction cost. The bottom and surface of the coating of the present invention are integrated, and multiple coats are changed into a single coat, which saves time and construction costs, is easy to construct, and can be constructed by a variety of methods such as a two-component pump, a single-component pump, brushing, and roller coating. It has a wide range of application prospects and can be used for steel structure facilities such as bridges, marine engineering, petrochemical plants, and engineering machinery. It is suitable for the corrosion protection of the inner walls of oil pipelines, natural gas pipelines, storage tanks, reservoirs, etc., and can resist the corrosion of the substrate by various gases and liquid media, and increase the corrosion resistance period.
[0034] 3. The present invention improves wear resistance and reduces resistance by modifying graphene and modified humic acid, and utilizes magnetization + instantaneous pressurization to bond the modified graphene powder and sulfomethylated humic acid carbon nanosheets to form a stable, dense and smooth structure, thereby preventing brittle cracking, enhancing the anti-corrosion performance of the coating, reducing wear resistance and drag, and extending the service life. DETAILED DESCRIPTION
[0035] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention. The experimental methods used in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial channels unless otherwise specified. The thickness of the graphene of the present invention is <3nm, the number of sheets is ≈100 trillion sheets / gram, and the purity is >96%. The acrylic emulsion or polyurethane emulsion of the present invention is purchased from Shanghai Xunda New Materials Technology Co., Ltd. The curing agent of the present invention is a modified fatty amine epoxy resin curing agent, which was purchased from Jiangyin Wanqian Chemicals Co., Ltd. The defoaming agent of the present invention was purchased from Guangdong Zhongke Hongtai New Materials Co., Ltd. The acid solution of the present invention is any one of hydrochloric acid, sulfuric acid or nitric acid.
[0036] Example 1
[0037] The graphene-based solvent-free wear-resistant and drag-reducing coating of this embodiment includes the following raw materials in parts by weight: 50 parts of resin (fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:1.5), 8 parts of modified graphene powder, 8 parts of sulfomethylated fulvic acid carbon nanosheets, 3 parts of acrylic emulsion, 2 parts of silicon dioxide, 0.7 parts of defoaming agent, and 7 parts of curing agent;
[0038] The modified graphene powder includes amino-modified graphene powder and alkyl-modified graphene powder in a mass ratio of 1:4; the preparation of amino-modified graphene powder: adding graphene to anhydrous ethanol according to a solid-liquid ratio of 1:70 g / mL, adding (3-aminopropyl)triethoxysilane, and the liquid-solid ratio of (3-aminopropyl)triethoxysilane to graphene is 4:1 ml / g, activating at 75°C for 8 hours, washing and drying, and obtaining alkyl-modified graphene. Preparation of graphene powder: add graphene to 0.08 mol / L acid solution at a solid-liquid ratio of 1:70 g / mL, condense and reflux at 90°C for 6 hours, wash and dry to obtain powder, add the powder to anhydrous ethanol at a solid-liquid ratio of 1:60 g / mL, add trimethylchlorosilane, the liquid-solid ratio of trimethylchlorosilane to powder is 4:1 ml / g, ultrasonically stir at 50 kHz and 50°C for 8 hours, wash and dry to obtain.
[0039] Preparation method of sulfomethylated fulvic acid carbon nanosheets:
[0040] (1) adding fulvic acid to 0.08 mol / L sodium hydroxide solution at a solid-liquid ratio of 1:15 g / mL, immersing at 23°C for 11 h, filtering, and obtaining pretreated fulvic acid;
[0041] (2) According to the solid-liquid ratio of 1:6 g / mL, the pretreated fulvic acid was added to a 25 wt% formaldehyde aqueous solution, the temperature was raised to 560 ° C, and the reaction was carried out for 45 minutes. Then, sodium pyrosulfite was added, and the mass ratio of sodium pyrosulfite to pretreated fulvic acid was 0.4:1. The temperature was further raised to 75 ° C, and the reaction was carried out for 3 hours. The mixture was filtered and dried to obtain sulfomethylated fulvic acid;
[0042] (3) Sulfomethylated humic acid was added to anhydrous ethanol at a solid-liquid ratio of 1:35 g / mL, and the mixture was ultrasonically treated at 250 rpm and 35 °C for 3 h. The mixture was filtered, freeze-dried, placed in a nitrogen atmosphere, and calcined at 450 °C for 45 min to obtain sulfomethylated humic acid carbon nanosheets.
[0043] The preparation method of the graphene-based solvent-free wear-resistant and drag-reducing coating of this embodiment has the following specific preparation steps:
[0044] (1) The modified graphene powder and 40 wt% of the acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain a dispersion a;
[0045] (2) The sulfomethylated fulvic acid carbon nanosheets and the remaining amount of acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain dispersion b;
[0046] (3) magnetizing the dispersion a and the dispersion b at 150 Gs for 25 min, and then instantaneously pressurizing (15 MPa) for 7 min, filtering and drying to obtain a mixture;
[0047] (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0048] Example 2
[0049] The graphene-based solvent-free wear-resistant and drag-reducing coating of this embodiment includes the following raw materials in parts by weight: 40 parts of resin (fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:1), 5 parts of modified graphene powder, 5 parts of sulfomethylated fulvic acid carbon nanosheets, 2 parts of acrylic emulsion, 1 part of silicon dioxide, 0.5 parts of defoaming agent, and 6 parts of curing agent;
[0050] The modified graphene powder includes amino-modified graphene powder and alkyl-modified graphene powder in a mass ratio of 1:3; the preparation of amino-modified graphene powder: adding graphene to anhydrous ethanol according to a solid-liquid ratio of 1:50 g / mL, adding (3-aminopropyl)triethoxysilane, and adding (3-aminopropyl)triethoxysilane to graphene in a liquid-solid ratio of 3:1 ml / g, activating at 70°C for 6 hours, washing and drying, and obtaining alkyl-modified graphene. Preparation of graphene powder: add graphene to 0.05 mol / L acid solution at a solid-liquid ratio of 1:60 g / mL, condense and reflux at 80°C for 5 hours, wash and dry to obtain powder, add the powder to anhydrous ethanol at a solid-liquid ratio of 1:50 g / mL, add trimethylchlorosilane, the liquid-solid ratio of trimethylchlorosilane to powder is 3:1 ml / g, ultrasonically stir at 40 kHz and 40°C for 6 hours, wash and dry to obtain.
[0051] Preparation method of sulfomethylated fulvic acid carbon nanosheets:
[0052] (1) adding fulvic acid to a 0.05 mol / L sodium hydroxide solution at a solid-liquid ratio of 1:10 g / mL, immersing at 20°C for 10 h, and filtering to obtain pretreated fulvic acid;
[0053] (2) According to the solid-liquid ratio of 1:5 g / mL, the pretreated humic acid was added to a 20 wt% formaldehyde aqueous solution, the temperature was raised to 40 ° C, and the reaction was carried out for 30 minutes. Then, sodium pyrosulfite was added, and the mass ratio of sodium pyrosulfite to pretreated humic acid was 0.3:1. The temperature was further raised to 70 ° C, and the reaction was carried out for 2 hours. The mixture was filtered and dried to obtain sulfomethylated humic acid;
[0054] (3) Sulfomethylated humic acid was added to anhydrous ethanol at a solid-liquid ratio of 1:20 g / mL, and the mixture was ultrasonically treated at 200 rpm and 30 °C for 2 h. The mixture was filtered, freeze-dried, placed in a nitrogen atmosphere, and calcined at 400 °C for 30 min to obtain sulfomethylated humic acid carbon nanosheets.
[0055] The preparation method of the graphene-based solvent-free wear-resistant and drag-reducing coating of this embodiment has the following specific preparation steps:
[0056] (1) The modified graphene powder and 30 wt% of the acrylic emulsion were mixed, shaken at 2000 rpm for 10 min, and irradiated with microwaves (400 W) for 5 min to obtain a dispersion a;
[0057] (2) The sulfomethylated fulvic acid carbon nanosheets and the remaining amount of acrylic emulsion were mixed, shaken at 2000 rpm for 10 min, and irradiated with microwaves (400 W) for 5 min to obtain dispersion b;
[0058] (3) magnetizing the dispersion a and the dispersion b at 100 Gs for 20 min, and then instantaneously pressurizing (10 MPa) for 5 min, filtering and drying to obtain a mixture;
[0059] (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0060] Example 3
[0061] The graphene-based solvent-free wear-resistant and drag-reducing coating of this embodiment includes the following raw materials in parts by weight: 60 parts of resin (fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:2), 10 parts of modified graphene powder, 10 parts of sulfomethylated fulvic acid carbon nanosheets, 4 parts of acrylic emulsion, 3 parts of silicon dioxide, 0.8 parts of defoaming agent, and 9 parts of curing agent;
[0062] The modified graphene powder includes amino-modified graphene powder and alkyl-modified graphene powder in a mass ratio of 1:5; the preparation of amino-modified graphene powder: adding graphene to anhydrous ethanol at a solid-liquid ratio of 1:100 g / mL, adding (3-aminopropyl)triethoxysilane, the liquid-solid ratio of (3-aminopropyl)triethoxysilane to graphene is 5:1 ml / g, activating at 80°C for 10 hours, washing and drying to obtain; alkyl-modified graphene Preparation of graphene powder: add graphene to 0.1 mol / L acid solution at a solid-liquid ratio of 1:80 g / mL, condense and reflux at 100°C for 7 hours, wash and dry to obtain powder, add the powder to anhydrous ethanol at a solid-liquid ratio of 1:70 g / mL, add trimethylchlorosilane, the liquid-solid ratio of trimethylchlorosilane to powder is 5:1 ml / g, ultrasonically stir at 60 kHz and 60°C for 10 hours, wash and dry to obtain.
[0063] Preparation method of sulfomethylated fulvic acid carbon nanosheets:
[0064] (1) adding fulvic acid to a 0.1 mol / L sodium hydroxide solution at a solid-liquid ratio of 1:20 g / mL, immersing at 25°C for 12 h, and filtering to obtain pretreated fulvic acid;
[0065] (2) According to the solid-liquid ratio of 1:7 g / mL, the pretreated fulvic acid was added to a 30 wt% formaldehyde aqueous solution, the temperature was raised to 60 ° C, and after reacting for 60 min, sodium pyrosulfite was added, and the mass ratio of sodium pyrosulfite to pretreated fulvic acid was 0.5:1. The temperature was further raised to 80 ° C, the reaction was continued for 4 h, and the mixture was filtered and dried to obtain sulfomethylated fulvic acid;
[0066] (3) Sulfomethylated humic acid was added to anhydrous ethanol at a solid-liquid ratio of 1:50 g / mL, and the mixture was ultrasonically treated at 300 rpm and 40 °C for 4 h. The mixture was filtered, freeze-dried, placed in a nitrogen atmosphere, and calcined at 500 °C for 60 min to obtain sulfomethylated humic acid carbon nanosheets.
[0067] The preparation method of the graphene-based solvent-free wear-resistant and drag-reducing coating of this embodiment has the following specific preparation steps:
[0068] (1) The modified graphene powder and 50 wt% acrylate emulsion were mixed, shaken at 3000 rpm for 20 min, and irradiated with microwaves (600 W) for 10 min to obtain a dispersion a;
[0069] (2) The sulfomethylated fulvic acid carbon nanosheets and the remaining amount of acrylic emulsion were mixed, shaken at 3000 rpm for 20 min, and irradiated with microwaves (600 W) for 10 min to obtain dispersion b;
[0070] (3) magnetizing the dispersion a and the dispersion b at 200 Gs for 30 min, and then instantaneously pressurizing (20 MPa) for 8 min, filtering and drying to obtain a mixture;
[0071] (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0072] Comparative Example 1
[0073] The difference from Example 1 is that the modified graphene powder is replaced by graphene, and the rest is consistent with Example 1.
[0074] The graphene-based solvent-free wear-resistant and drag-reducing coating of this comparative example includes the following raw materials in parts by weight: 50 parts of resin (fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:1.5), 8 parts of graphene, 8 parts of sulfomethylated fulvic acid carbon nanosheets, 3 parts of acrylic emulsion, 2 parts of silicon dioxide, 0.7 parts of defoaming agent, and 7 parts of curing agent;
[0075] The preparation method of sulfomethylated fulvic acid carbon nanosheets is as follows:
[0076] (1) adding fulvic acid to 0.08 mol / L sodium hydroxide solution at a solid-liquid ratio of 1:15 g / mL, immersing at 23°C for 11 h, filtering, and obtaining pretreated fulvic acid;
[0077] (2) According to the solid-liquid ratio of 1:6 g / mL, the pretreated fulvic acid was added to a 25 wt% formaldehyde aqueous solution, the temperature was raised to 560 ° C, and the reaction was carried out for 45 minutes. Then, sodium pyrosulfite was added, and the mass ratio of sodium pyrosulfite to pretreated fulvic acid was 0.4:1. The temperature was further raised to 75 ° C, and the reaction was carried out for 3 hours. The mixture was filtered and dried to obtain sulfomethylated fulvic acid;
[0078] (3) Sulfomethylated humic acid was added to anhydrous ethanol at a solid-liquid ratio of 1:35 g / mL, and the mixture was ultrasonically treated at 250 rpm and 35 °C for 3 h. The mixture was filtered, freeze-dried, placed in a nitrogen atmosphere, and calcined at 450 °C for 45 min to obtain sulfomethylated humic acid carbon nanosheets.
[0079] The preparation method of the graphene-based solvent-free wear-resistant and drag-reducing coating of this comparative example has the following specific preparation steps:
[0080] (1) Graphene and 40 wt% of acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain dispersion a;
[0081] (2) The sulfomethylated fulvic acid carbon nanosheets and the remaining amount of acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain dispersion b;
[0082] (3) magnetizing the dispersion a and the dispersion b at 150 Gs for 25 min, and then instantaneously pressurizing (15 MPa) for 7 min, filtering and drying to obtain a mixture;
[0083] (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0084] Comparative Example 2
[0085] The difference from Example 1 is that the sulfomethylated fulvic acid carbon nanosheets are missing, and the rest is the same as Example 1.
[0086] The graphene-based solvent-free wear-resistant and drag-reducing coating of this comparative example includes the following raw materials in parts by weight: 50 parts of resin (fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:1.5), 16 parts of modified graphene powder, 3 parts of acrylic emulsion, 2 parts of silicon dioxide, 0.7 parts of defoaming agent, and 7 parts of curing agent;
[0087] The modified graphene powder includes amino-modified graphene powder and alkyl-modified graphene powder in a mass ratio of 1:4;
[0088] Preparation of amino-modified graphene powder: add graphene to anhydrous ethanol at a solid-liquid ratio of 1:70 g / mL, add (3-aminopropyl)triethoxysilane, and the liquid-solid ratio of (3-aminopropyl)triethoxysilane to graphene is 4:1 ml / g, activate at 75°C for 8 hours, wash and dry to obtain;
[0089] Preparation of alkyl-modified graphene powder: add graphene to 0.08 mol / L acid solution at a solid-liquid ratio of 1:70 g / mL, condense and reflux at 90°C for 6 hours, wash and dry to obtain powder, add the powder to anhydrous ethanol at a solid-liquid ratio of 1:60 g / mL, add trimethylchlorosilane, the liquid-solid ratio of trimethylchlorosilane to powder is 4:1 ml / g, ultrasonically stir at 50 kHz and 50°C for 8 hours, wash and dry to obtain.
[0090] The preparation method of the graphene-based solvent-free wear-resistant and drag-reducing coating of this comparative example has the following specific preparation steps:
[0091] (1) The modified graphene powder and the acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain a dispersion;
[0092] (2) magnetizing the dispersion at 150 Gs for 25 min, then instantaneously pressurizing (15 MPa) for 7 min, filtering and drying to obtain a mixture;
[0093] (3) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0094] Comparative Example 3
[0095] The difference from Example 1 is that the resin is epoxy resin, and the rest is the same as Example 1.
[0096] The graphene-based solvent-free wear-resistant and drag-reducing coating of this comparative example comprises the following raw materials in parts by weight:
[0097] 50 parts of epoxy resin, 8 parts of modified graphene powder, 8 parts of sulfomethylated fulvic acid carbon nanosheets, 3 parts of acrylic emulsion, 2 parts of silicon dioxide, 0.7 parts of defoaming agent, and 7 parts of curing agent.
[0098] Comparative Example 4
[0099] The difference from Example 1 is that the magnetization and instantaneous pressurization treatment are missing, and the rest is the same as Example 1.
[0100] The preparation method of the graphene-based solvent-free wear-resistant and drag-reducing coating of this comparative example has the following specific preparation steps:
[0101] (1) The modified graphene powder and 40 wt% of the acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain a dispersion a;
[0102] (2) The sulfomethylated fulvic acid carbon nanosheets and the remaining amount of acrylic emulsion were mixed, shaken at 2500 rpm for 15 min, and irradiated with microwaves (500 W) for 8 min to obtain dispersion b;
[0103] (3) Mixing the dispersion a and the dispersion b, filtering and drying to obtain a mixture;
[0104] (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
[0105] Test Example 1
[0106] The graphene solvent-free wear-resistant and drag-reducing coating is airless sprayed, and is used under temperature conditions above 5°C for normal construction and curing. The substrate temperature should be higher than 10°C, the paint temperature should be higher than 20°C, the surface temperature must always be kept at least 3°C above the dew point, and the relative humidity should not be greater than 85%. The surface of the construction substrate must be kept clean and dry, and ventilation must be ensured during construction in a confined space. The performance of the graphene-based solvent-free wear-resistant and drag-reducing coatings of Examples 1-3 was tested, and the test standards and results are shown in Table 1.
[0107] Table 1
[0108]
[0109] It can be seen from Table 1 that the various properties of the graphene-based solvent-free wear-resistant and drag-reducing coating of the present invention meet the index standards, and have excellent wear resistance and show super wear resistance, which is more than 2.5 times higher than the standard requirement, high adhesion, impermeability, delaying the invasion of corrosion factors into the surface of the substrate, showing super corrosion resistance, acid resistance, alkali resistance and salt resistance, and are suitable for various corrosive environments such as extremely corrosive atmospheric environment, seawater, fresh water, drinking water, soil burial, acid and alkali chemical immersion, etc.
[0110] Test Example 2
[0111] Test object: Pumped storage penstock
[0112] Test background: The pressure steel pipes in the water delivery systems of conventional hydropower stations and pumped storage power stations are usually subjected to high internal water pressure. The high-pressure environment places extremely high demands on the mechanical strength and corrosion resistance of the coating. The coating not only needs to maintain structural integrity under long-term water pressure, but also must be able to withstand multiple high-pressure water scouring. In this high-pressure environment, the volatilization of solvents in a confined space may lead to safety risks such as explosion or suffocation of personnel, and the precipitation of volatiles may also pollute the water quality. In addition, after years of operation, scale may accumulate on the inner wall of the steel pipe, as well as the growth of algae and other microorganisms, which will increase the resistance inside the pipe and affect the water flow rate. In seawater pumped storage power stations, it is also necessary to face the adsorption of marine algae and other marine organisms, the presence of which will also significantly increase the flow resistance of the pipeline.
[0113] Construction method: Spraying technology is used, the coating thickness is 200μm. After construction, the coating can be quickly cured at room temperature, and the curing time is 24 hours.
[0114] 1. High pressure flow performance test
[0115] The initial flow rate was set to 1000 mm / s, the water pressure was 1000 MPa, and the pressure loss of the sample tubes not coated with the coating and the sample tubes coated with the graphene-based solvent-free wear-resistant and drag-reducing coatings of Examples 1-3 and Comparative Examples 1-4 at the same flow rate of 1000 mm / s was calculated. The results are shown in Table 2.
[0116] Table 2
[0117]
[0118] 2. Drag reduction effect test
[0119] The sample tube size is Ф50×1000mm, the water pressure is 1000Mpa, and the flow velocity (mm / s) of the fluid in the uncoated channel and the drag reduction coating channel is recorded, and the drag reduction rate is calculated.
[0120] The drag reduction rate calculation formula is: drag reduction rate = (drag reduction coating channel flow velocity - uncoated channel flow velocity) / drag reduction coating channel flow velocity.
[0121] The results are shown in Table 3.
[0122] Table 3
[0123]
[0124] It can be seen from Table 3 that the graphene-based solvent-free wear-resistant drag-reducing coatings of Examples 1-3 of the present invention have good drag-reducing effects, while the drag-reducing effects of Comparative Examples 1-4 are reduced.
[0125] 3. Wear resistance test
[0126] Abrasion resistance is tested by spraying a high-speed air stream containing abrasives onto the coating surface;
[0127] Air velocity: 70 m•s -1 ; Abrasive type: standard silica sand, particle size 200-300μm;
[0128] Spraying time: Each test sample was sprayed continuously for 5 minutes; Spraying distance: The distance from the nozzle to the sample surface was fixed at 50 cm.
[0129] After the test, the coating surface will be visually inspected to evaluate the wear condition, and the reduction in coating thickness will be measured to quantitatively analyze the degree of wear, wear rate = (coating thickness before test - coating thickness after test) / coating thickness before test. The wear resistance of the coating is further verified by comparing the mass change of the coating before and after the test, mass loss rate = (coating mass before test - coating mass after test) / coating mass before test.
[0130] The results are shown in Table 4.
[0131] Table 4
[0132]
[0133] It can be seen from Table 4 that the coatings prepared in Examples 1-3 of the present invention exhibit excellent wear resistance and good stability under high-speed abrasive impact.
[0134] The test items and test conditions of long-term stability test are shown in Table 5.
[0135] Table 5
[0136]
[0137] The test results are shown in Table 6.
[0138] Table 6
[0139]
[0140] It can be seen from Table 6 that the coatings prepared in Examples 1-3 of the present invention have good long-term stability.
[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A graphene-based solvent-free wear-resistant and drag-reducing coating, characterized in that: The raw materials include the following in parts by weight: 40-60 parts of resin, 5-10 parts of modified graphene powder, 5-10 parts of sulfomethylated fulvic acid carbon nanosheets, 2-4 parts of polymer emulsion, 1-3 parts of silicon dioxide, 0.5-0.8 parts of defoaming agent, and 6-9 parts of curing agent; Wherein, the resin is composed of fluorocarbon resin and phenolic epoxy resin in a mass ratio of 1:1-2; The modified graphene powder includes amino-modified graphene powder and alkyl-modified graphene powder in a mass ratio of 1:3-5; The preparation method of the amino-modified graphene powder comprises: adding graphene into anhydrous ethanol, adding (3-aminopropyl)triethoxysilane for activation, washing and drying to obtain; The preparation method of the alkyl-modified graphene powder comprises: adding graphene to an acid solution for condensation and reflux, washing and drying to obtain powder, adding the powder to anhydrous ethanol, adding trimethylsilyl chloride, ultrasonically stirring, washing and drying to obtain the powder; The preparation method of the sulfomethylated fulvic acid carbon nanosheets comprises: (1) adding fulvic acid into a sodium hydroxide solution for immersion, filtering, and obtaining pretreated fulvic acid; (2) adding the pretreated fulvic acid to the formaldehyde aqueous solution, heating the reaction, adding sodium pyrosulfite, continuing to heat the reaction, filtering and drying, and obtaining sulfomethylated fulvic acid; (3) Add sulfomethylated fulvic acid into anhydrous ethanol, perform ultrasonic treatment, filter, freeze-dry, and calcine under a nitrogen atmosphere to obtain sulfomethylated fulvic acid carbon nanosheets.
2. A graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 1, characterized in that: In the preparation method of the amino-modified graphene powder, the solid-liquid ratio of the graphene to anhydrous ethanol is 1:50-100 g / mL; the liquid-solid ratio of the (3-aminopropyl)triethoxysilane to the graphene is 3-5:1 ml / g; and the activation is performed at 70-80° C. for 6-10 hours.
3. A graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 1, characterized in that: In the preparation method of alkyl-modified graphene powder, the solid-liquid ratio of the graphene to the acid solution is 1:60-80 g / mL; the concentration of the acid solution is 0.05-0.1 mol / L; the acid solution is any one of hydrochloric acid, sulfuric acid or nitric acid; the reflux temperature is 80-100°C and the time is 5-7h; the solid-liquid ratio of the powder to anhydrous ethanol is 1:50-70 g / mL; the liquid-solid ratio of trimethylchlorosilane to the powder is 3-5:1 ml / g; and the ultrasonic stirring is performed at 40-60 kHz and 40-60°C for 6-10h.
4. A graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 1, characterized in that: In the preparation method of sulfomethylated fulvic acid carbon nanosheets, in step (1), the solid-liquid ratio of fulvic acid to sodium hydroxide solution is 1:10-20 g / mL; the concentration of the sodium hydroxide solution is 0.05-0.1 mol / L; the immersion is carried out at 20-25° C. for 10-12 hours; In step (2), the solid-liquid ratio of the pretreated fulvic acid to the formaldehyde aqueous solution is 1:5-7 g / mL; the concentration of the formaldehyde aqueous solution is 20-30 wt%; the temperature-raising reaction is carried out at 40-60° C. for 30-60 min; the mass ratio of the sodium pyrosulfite to the pretreated fulvic acid is 0.3-0.5:1; and the continued temperature-raising reaction is carried out at 70-80° C. for 2-4 h; In step (3), the solid-liquid ratio of the sulfomethylated fulvic acid to anhydrous ethanol is 1:20-50 g / mL; the ultrasonic treatment is performed at 200-300 rpm and 30-40° C. for 2-4 hours; the calcination temperature is 400-500° C. and the calcination time is 30-60 minutes.
5. A graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 1, characterized in that: The polymer emulsion is an acrylic emulsion or a polyurethane emulsion.
6. The method for preparing a graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 1, characterized in that: The specific preparation steps are as follows: (1) mixing and oscillating the modified graphene powder and a polymer emulsion having a formula amount of 30-50 wt%, and simultaneously irradiating with microwaves to obtain a dispersion a; (2) mixing and oscillating the sulfomethylated fulvic acid carbon nanosheets and the remaining polymer emulsion, and simultaneously irradiating with microwaves to obtain a dispersion b; (3) magnetizing the dispersion a and the dispersion b, instantaneously pressurizing them after magnetization, filtering and drying them to obtain a mixture; (4) Mix the mixture with resin, silica, defoamer and curing agent, and stir evenly to obtain the product.
7. The method for preparing a graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 6, characterized in that: In steps (1) and (2), the oscillation is carried out at 2000-3000 rpm for 10-20 min; the power of the microwave radiation is 400-600 W, and the time is 5-10 min.
8. The method for preparing a graphene-based solvent-free wear-resistant and drag-reducing coating according to claim 6, characterized in that: In step (3), the intensity of the magnetization treatment is 100-200 Gs, and the time is 20-30 min; the pressure of the instantaneous pressurization is 10-20 MPa, and the time is 5-8 min.
Citation Information
Patent Citations
Graphene type solvent-free inner drag reduction coating and a preparing method thereof
CN108373738A
Preparation method of nitrogen-doped fulvic acid-based porous carbon adsorption material
CN110339817A
Preparation method and application of biomass-based carbon nanosheet / epoxy composite coating
CN112430418A